2022
DOI: 10.3390/ijms23116166
|View full text |Cite
|
Sign up to set email alerts
|

LXRα Regulates oxLDL-Induced Trained Immunity in Macrophages

Abstract: Reprogramming of metabolic pathways in monocytes and macrophages can induce a proatherosclerotic inflammatory memory called trained innate immunity. Here, we have analyzed the role of the Liver X receptor (LXR), a crucial regulator of metabolism and inflammation, in oxidized low-density lipoprotein (oxLDL)-induced trained innate immunity. Human monocytes were incubated with LXR agonists, antagonists, and oxLDL for 24 h. After five days of resting time, cells were restimulated with the TLR-2 agonist Pam3cys. Ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Furthermore, LXR activation inhibits the production of a series of pro-inflammatory factors which are stimulated by bacteria, bacterial endotoxin lipopolysaccharide (LPS), TNF-α, and IL-1β. LXR agonists play an important regulatory role in inhibiting the expression of proinflammatory genes in macrophages and other types of cells (Findeisen et al, 2022). LXRα can selectively regulate the expression of genes related to apoptosis and leukocyte migration.…”
Section: Mechanisms Of Action Of Lxr Signaling Pathwaymentioning
confidence: 99%
“…Furthermore, LXR activation inhibits the production of a series of pro-inflammatory factors which are stimulated by bacteria, bacterial endotoxin lipopolysaccharide (LPS), TNF-α, and IL-1β. LXR agonists play an important regulatory role in inhibiting the expression of proinflammatory genes in macrophages and other types of cells (Findeisen et al, 2022). LXRα can selectively regulate the expression of genes related to apoptosis and leukocyte migration.…”
Section: Mechanisms Of Action Of Lxr Signaling Pathwaymentioning
confidence: 99%
“…Their increased responsiveness could contribute to the development and/or maintenance of chronic or recurrent inflammation and tissue destruction, which characterize autoinflammatory and autoimmune diseases. The initial stimulus leading to or fueling autoinflammatory and autoimmune diseases remain to be identified, but trained immunity can be induced by endogenous and environmental stimuli, such as oxidized lowdensity lipoprotein (oxLDL) and western diet (115)(116)(117), that are also known or suspected to participate to the development of autoinflammatory and autoimmune diseases (118,119). Consequently, strategies targeting metabolism and epigenetic reprogramming, which represent the hallmarks of trained immunity, are being proposed as potential treatments or prevention strategies of autoinflammation and autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of fatty acids are sensed as danger signals by PRRs such as the Nod‐like receptor family pyrin domain containing 3 (NLRP3) and toll‐like receptors (TLRs), which stimulate inflammatory responses against further stimuli 71,75 . Accordingly, oxidized low‐density lipoprotein (oxLDL) enhances glycolytic activity and induces innate immune memory in macrophages, thus suggesting the essential role of glycolysis and lipid synthesis pathways in forming the immune memory phenotype 73,76,77 . Apart from these, the involvement of other metabolic pathways (e.g., pentose phosphate pathways and amino acid metabolic pathways) in innate immune memory has also been reviewed in detail 78,79 …”
Section: Mechanismsmentioning
confidence: 99%
“…71,75 Accordingly, oxidized low-density lipoprotein (oxLDL) enhances glycolytic activity and induces innate immune memory in macrophages, thus suggesting the essential role of glycolysis and lipid synthesis pathways in forming the immune memory phenotype. 73,76,77 Apart from these, the involvement of other metabolic pathways (e.g., pentose phosphate pathways and amino acid metabolic pathways) innate immune memory has also been reviewed in detail. 78,79 It is still poorly understood how cellular metabolism connects to epigenetic memory in innate immunity, although it is suggested that some products of the TCA cycle (e.g., acetyl-CoA) might be involved in histone modifications during immune memory (Figure 2).…”
Section: Metabolism Pathwaysmentioning
confidence: 99%